Development and Implementation of Electronic Applications based on Arduino Platform for a First Basic Course - Trujillo-Aguilera, Davinia; Blázquez-Parra, Elidia Beatriz; Palomares Vigil, Antonio; Marín Bao, Teresa (My University, 2019)
This paper shows a learning guide about the use of Arduino platform and the different utilities that can be implemented based on this platform for a first basic course. The paper can be useful as a guide for someone who wants to start in the world of microcontroller programming, with examples to consolidate the knowledge learned. Some students of the School of Industrial Engineering of the University of Malaga (Degree in Industrial Design) approach the study of an engineering career with little knowledge of electronics. This degree contains basic skills on learning electronics and the use of the Arduino platform and its development possibilities can offer students an interesting view of electronics, making better use of classes. The work is based on both theoretical (to make the components known) and practical (using real assemblies) development to consolidate the knowledge learned. Therefore, once the basic components necessary to carry out various practices have been explained, the theoretical performance and the programming of Arduino is explained and the various practices that will be set up in the laboratory are presented, as an application of Arduino for different uses. The main idea of this work is to replace the traditional laboratory practices that require more advanced knowledge in electronics with a set of simple practices carried out in Arduino that allow students to have an approximate idea of basic electronics with little knowledge. After three years of carrying out this new methodology for this first basic electronic course, the surveys demonstrate a better adaptation of the students to the study of electronics. In addition, the marks obtained have improved considerably and the students have the sensation of learning electronics in a simple and fun way.
Keywords: Electrónica-Estudio y enseñanza; Enseñanza universitaria; Enseñanza superior; Diseño industrial-Estudio y enseñanza; ICT; Educational innovation; Arduino; Basic Electronics; Industrial Design